(untitled) (OODBODHAN, 2024)
The wind tunnel is an arrangement to simulate real aerodynamic parameters. An open circuit wind tunnel does not circulate the same fluid as working fluid rather uses environmental fluid circulated by a fan. This research paper documents the design, construction, and setup of a low-speed subsonic open wind tunnel at the National Innovation Center, Kirtipur. This wind tunnel produces a controlled stream of air to test the aerodynamic properties of objects or fluids. The wind tunnel developed at NIC is used for a variety of research activities related to the aerodynamics of different bodies such as testing of lift coefficient, drag coefficient, and pressure difference calculations on drones and rockets along with flow visualization in civil works signature bridges and high-rise buildings. Designed to be a general-purpose wind tunnel, it is the biggest of its kind in Nepal.